Reinventing treaty compliant ''safety zones'' in the context of space sustainability. Issue 2 (June 2021) - Mallowan, Lucas; Rapp, Lucien; Topka, Maria
Abstract: This paper questions the concept of safety zones, tracing it to maritime and military law, in order to unpack its potential legal uses, applications and implications in the current context of the New Space economy. To achieve this, it starts by investigating the historical foundations of safety zones rooted in the Cold-War-era legal literature and then move on to a larger discussion of how such zones can be balanced with the non-appropriation principle. Then, this paper examines a number of legal analogies, as they appear in maritime law, aviation law as well as relevant examples in outer-space law. Lastly, it attempts to sketch the outline of a "solution" that identifies the criteria, to be used in order to model a potential safety zone that strikes a balance between the industry's growing concerns and requirements on one hand, and the legal prohibitions that preclude sovereign claims on outer space on the other hand. Particular attention is given to the special case of the United States' extraterritorial jurisdiction in outer space.